Analisis Kesiapan Penerapan E-learning di Sekolah Dasar Menggunakan E-learning Readiness Model: Studi kasus Madrasah Islamiyah Darwata Karangasem - Mirza Ali Arsyad; Yudha Saintika; Resad Setyadi (Universitas Merdeka Malang, 2021)
In 2020, the world was shocked by the covid-19 virus, which has spread to all countries of the world, including Indonesia. In education, almost all schools in Indonesia have been forced to close by the government and replaced with distance learning. However, in many schools there are obstacles such as the inability of teachers and students to use technology. One of the problems in Islamiya Darwata Karangasem Madrasah. The purpose of this study was to determine the relationship between environmental, teacher, technology and student readiness and provide recommendations for schools to be more prepared to implement distance learning. The method used in this study is a descriptive analysis with an e-readiness model. The sample in this study consisted of 52 students and 9 teachers. The results showed that an overall ELR score of 3.62288 was included in the readiness category, but needed some improvement. The teacher had a score of 3.79167, which was classified as readiness, but needed some improvement. , which was included in 64814, is categorized as finished but needs work, and the technology is rated 3.48148, which means it's ready but needs a little improvement. By improving school internet speeds, evaluating student learning, providing new policies, changing individual perspectives, and increasing budgets.